Perception of customers splurging the prospects of bancassurance: evidence from Indian banking firms. (30th June 2022) - Agrawal, Rachna; Gupta, Riya
Bancassurance is the term assimilating a lot of potential gains for both banks and insurance companies. Being a convention, there is still a high scope to attain success in the financial sector of an economy. This study highlights the perceptions of customers buying insurance products through banks. Responses of 250 customers availing the insurance products through bancassurance are compiled through a self-designed structured questionnaire with a seven-point Likert scale. Due to the non-normality of the data, partial least squares-structural equation modelling (PLS-SEM) has been employed through Smart PLS software. A review of gathered data directing towards a positive relationship among constructs is tested. The study confirms a significant strong relationship among all constructs except product knowledge and customer loyalty (CL) where a weak association has been found. It is interesting to observe the constructs and their relationship with customers' attitude (CA) and customers' loyalty (CL). In addition, the relationship between CA and CL has provided new insights to the literature.